Sengkelan Kanong (Perwujudan Rasa Syukur Atas Kehamilan) Kajian Kearifan Lokal Masyarakat Melayu Sintang - Suryadi, Tedi; Fitrianingrum, Evi; Tyas, Debora Korining (Universitas Muhammadiyah Surabaya, 2024)
The goal of this research is to provide an overview of the Sengkelan Kanong implementation process. There has never been any research done on Sengkelan Kanong in the Sintang Malay Community. Therefore, there isn't any documentation regarding the Sengkelan Kanong customs. Researching and documenting Sengkelan Kanong, a seven-month practice that blends Islamic religious teachings with indigenous knowledge, is highly intriguing. The Sengkelan Kanong process is the research object, descriptive research method, and qualitative research strategy. Techniques for gathering data include observation, documentation, and interviews. Technical triangulation and interactive data analysis are used to test the data's veracity. The study's findings, which include 1) Sengkelan Kanong preparation; 2) Sengkelan Kanong tradition implementation requirements; and 3) Sengkelan Kanong tradition implementation costs, 4) Objects Used in the Sengkelan Kanong Tradition, 5) Materials Used in the Sengkelan Kanong Tradition, 6) Implementation Process Sengkelan Kanong Tradition.